Chronic Osteomyelitis of the Jaw: Pivotal Role of Microbiological Investigation and Multidisciplinary Management-A Case Report - Quentin Lucidarme; Delphine Lebrun; Véronique Vernet-Garnier; Joey Le Gall; Saïdou Diallo; Cédric Mauprivez; Stéphane Derruau (MDPI AG, 2022)
A 15-year-old girl with a history of recurrent painful orofacial swelling was diagnosed on the basis of clinical findings, histopathological examination and imaging modalities as having primary chronic osteomyelitis of the jaw. Initial microbiological samples were performed but were inconclusive. She received multiple empirical antibiotic therapies and NSAIDs for 3 years without complete remission. Only MALDI-TOF (Matrix-Assisted Laser Desorption/Ionization-Time Of Flight) analysis after additional multiple microbiological bone samples with adequate techniques yielded the final diagnosis of bacterial chronic osteomyelitis of the jaw. Its management requires a multidisciplinary approach, involving oral and maxillofacial surgeons, infectiologists and microbiologists, to limit treatment failure. Antibiotic therapy without surgery for 6 months achieved the complete radiographic resolution of the CBCT (Cone Beam Computed Tomography) and the normalization of laboratory tests. After 2 years of follow-up, no relapse had been reported. Modern microbiological investigation and sampling techniques are critical for the accurate diagnosis and management of osteomyelitis of the jaw, especially in unusual and clinically misleading forms of this infection.